Classical Insights, Contemporary Relevance: Understanding Tafsir bi-al-Mathur in Quranic Studies - Md. Mahdi Hasan; Choirul Ahmad; Md. Rafiqul Islam (Studia Quranika, 2025)
This paper explores tafsir bi-al-mathur, or tradition-based Quranic exegesis, examining its core elements, interpretive diversity, and relevance in both historical and contemporary contexts. Defined by reliance on the Quran itself, prophetic traditions, and the interpretations of the Companions and Successors, tafsir bi-al-mathur is foundational in Islamic scholarship for preserving original meanings of the Quran. However, its dependence on early sources raises questions about its adaptability to current ethical, legal, and social issues within Muslim communities. Through a qualitative analysis, this study investigates primary interpretative methods within tafsir bi-al-mathur, including tafsir al-Quran bi-l-Quran, tafsir bi-al-hadith, and interpretations by the Companions and Successors. The paper reveals how tafsir bi-al-mathur maintains Quranic authenticity while offering insights into its potential relevance for contemporary applications. This study contributes to Quranic studies by affirming tafsir bi-al-mathur as both a resilient and adaptable approach, balancing fidelity to foundational texts with interpretive flexibility in modern Islamic discourse.